Ultrawideband Technology in Medicine: A Survey. (9th April 2012) - Chávez-Santiago, R.; Balasingham, I.; Bergsland, J.
Abstract : The utilization of wireless technology in traditional medical services provides patients with enhanced mobility. This has a positive effect on the recovery speed of a person after major surgical procedures or prolonged illness. Ultrawideband (UWB) radio signals have inherent characteristics that make them highly suitable for less invasive medical applications. This paper surveys our own and related recent research on UWB technology for medical sensing and communications. Some research perspectives in the aforementioned topics are suggested too.